Modeling approach to the elements of TQM practice - Basmenj, Fazlollah Agamohamadi; Mohd Yusuff, Rosnah; Zulkifli, Norzima; Ismaiel, Yusof; Sorooshian, Shahryar (Trans Tech Publications, 2013)
This paper considers three factors; the selection of the Performance Measures, selection of the Critical Success Factors, and selection of quality tools as three elements of TQM. The qualitative research of this study tries to find and model the interrelation between elements of Total Quality Management (TQM) practice in companies.